PENYELESAIAN SENGKETA KEPEMILIKAN TANAH PADA KANTOR PERTANAHAN KOTA SOLOK (STUDI KASUS SENGKETA TANAH ANTARA PT GELORA GANTO SEJAHTERA DAN SYAMSU TULUS) - Fahmi Akbar NR; Kurnia Warman; Syofirman Syofyan (LPPM Universitas Ekasakti Padang, 2023)
Soil is one part of the earth that has a close relationship with human life, it can even be said that every human being is related to land. Article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia stipulates that: Earth, air and the natural resources contained therein are controlled by the State and used for the greatest prosperity of the people. However, land disputes still arise in the community, therefore this thesis takes the title of land ownership dispute resolution at the Solok City Land Office (a case study of land disputes between PT Gelora Ganto Sejahtera and Syamsu Tulus). In this writing, the problem formulation is 1. How to settle land disputes at the Solok City Land Office. 2 How is the authority of the Solok City land office in resolving land disputes. 3. What are the results of land dispute resolution at the Solok City Land Office. In writing this research, the method used is empirical juridical. Empirical juridical research is an approach by looking at a legal reality in society. The research conducted in this paper is descriptive analytical in nature, namely a form of research that aims to describe the applicable laws and regulations, associated with legal theories and the practice of implementing positive law. Disputes are situations and conditions in which people experience factual conflict or release according to their warnings. Land disputes can be resolved in 3 (three) ways, namely: a) Settlement by deliberation. b) Settlement through the judiciary, namely submitted to the general court in a civil or criminal manner. Based on this research, there is a land rights dispute that has been issued with a building use rights certificate in the name of PT. GGS entered. Then Samsyu Tulus objected that the settlement was carried out at the Solok City Land Office, then the settlement was not reached so that it entered the litigation route or went to court, from this research it was concluded that the Land Dispute Settlement in Solok City could be carried out on the basis of public complaints. The results of the mediation that have been agreed upon will result in changes to data, which can be in the form of a decision to cancel land rights, cancel certificates and also change data on certificates, measurement papers, land books and/or other public registers.